Phosphatidylethanol in whole blood of rhesus monkeys correlates with ethanol consumption. (19th April 2021) - Lopez‐Cruzan, Marisa; Walter, Nicole A. R.; Sanchez, Jesus J.; Ginsburg, Brett C.; Koek, Wouter; Jimenez, Vanessa A.; Grant, Kathleen A.; Javors, Martin A.
Abstract: Background: Phosphatidylethanol (PEth) homologs are ethanol metabolites used to identify and monitor alcohol drinking in humans. In this study, we measured levels of the 2 most abundant homologs, PEth 16:0/18:1 and PEth 16:0/18:2, in whole blood samples from rhesus macaque monkeys that drank ethanol daily ad libitum to assess the relationship between PEth levels and recent ethanol exposure in this animal model. Methods: Blood samples were obtained from The Monkey Alcohol Tissue Research Resource. The monkeys were first induced to consume 4% (w/v) ethanol in water from a panel attached to their home cage. Then, monkeys were allowed to drink ethanol and water ad libitum 22 h daily for 12 months and the daily amount of ethanol each monkey consumed was measured. Whole, uncoagulated blood was collected from each animal at the end of the entire experimental procedure. PEth 16:0/18:1 and PEth 16:0/18:2 levels were analyzed by HPLC with tandem mass spectrometry, and the ethanol consumed during the preceding 14 days was measured. Combined PEth was the sum of the concentrations of both homologs. Results: Our results show that (1) PEth accumulates in the blood of rhesus monkeys after ethanol consumption; (2) PEth homolog levels were correlated with the daily average ethanol intake during the 14‐day period immediately preceding blood collection; (3) the application of established human PEth 16:0/18:1 cutoff concentrations indicative of light social or no ethanol consumption (<20 ng/ml), moderate ethanol consumption (≥ 20 and < 200 ng/ml) and heavy ethanol consumption (≥ 200 ng/ml) predicted significantly different ethanol intake in these animals. PEth homologs were not detected in ethanol‐naïve controls. Conclusions: This study confirms that PEth is a sensitive biomarker for ethanol consumption in rhesus macaque monkeys. This nonhuman primate model may prove useful in evaluating sources of variability previously shown to exist between ethanol consumption and PEth homolog levels among humans. Abstract : This novel study shows that PEth, a direct biomarker of ethanol intake, is present in the blood of Rhesus monkeys after consuming ethanol ad libitum; and that the levels of the two most abundant PEth homologs, PEth 16:0/18:1 and PEth 16:0/18:2, are detectable as a function of daily ethanol consumed. This pre‐clinical model provides a greater experimental control over ethanol dosing, which could help understand and interpret variability found in PEth in human blood samples.